Social inequality and its impact on life expectancy. - Andrade, Flavia Cristina Drumond (Revista Kairós-Gerontologia, 2020)
Brazil has experienced a pronounced aging of its population with marked gains in life expectancy among older adults. However, individuals of lower socioeconomic conditions often exhibit worse health outcomes that translate in lower life expectancy and fewer years in good health. In this presentation, I examine how education influence prevalence of chronic conditions, life expectancy and life expectancy in good health.